On the Importance of Inhibition: Central and Peripheral Manifestations of Nonlinear Inhibitory Processes in Neural Systems - Julian F. Thayer (SAGE Publishing, 2006)
Inhibitory processes provide for the sculpting of neural action at all levels of the neuraxis. Importantly, it appears that this inhibitory function may be decidedly nonlinear in nature such that a little inhibition goes a long way in guiding the behavior of neural systems. The neural control of the heart is used as a model system to illustrate the nature of this nonlinear inhibitory control. Similar inhibitory processes function in the prefrontal cortex, in the amygdala, and between the prefrontal cortex and the amygdala in the service of organism flexibility, adaptability, and health. It is suggested that a dynamical systems perspective of neural regulation involving nonlinear inhibitory processes may be a useful framework within which to investigate the complex behavior associated with health and disease.